PAPR Reduction Method based on In-phase/Quadrature Data Symbol Components in MIMO-OFDM Systems - I. Al-Rayif, Mohammed (Array, 2021)
To overcome unpredictable spikes in the peak-toaverage power ratio (PAPR) in the presence of an orthogonal frequency-division multiplexing (OFDM) for multi-input-multioutput (MIMO) systems, implementation of a new SLM scheme is presented in this paper, which is extended from our previous study of IQ-SLM in SISO-OFDM system. In each transmit antenna, both real and imaginary parts of the base-band data symbol were modified independently using a corresponding phase element within a commonly generated phase vector, instead of modifying the complex data symbol as a single component. After applying an inverse fast Fourier transform (IFFT) for the real, imaginary, and original base-band vectors, the minimum PAPR component was observed. Therefore, the phase vector that introduced the minimal PAPR was considered to convert the original data block for transmission. This technique is called the In-phase/Quadrature-SLM (IQ-SLM) scheme. In this proposal, only U phase vectors were generated to treat all Nt data blocks, simultaneously, unlike the conventional MIMO-SLM techniques which generate UNt candidate phase blocks. The thing which, in turn, can be considered as a further computational complexity reduction, specifically in data-phase conversion stages. As a result, in terms of the complementary cumulative distribution function of PAPR performance(CCDF-PAPR), the proposal achieved a greater decibel reduction than conventional SLM methods such as dSLM, oSLM, and sSLM, at different subcarrier lengths N, candidate phase vectors U, transmit antennas Nt. Also, it shows a comparable BER performances over the dSLM scheme referencing to the theoretical curves, in the case where Nt ≤ Nr for both zero-forcing (ZF) and ZF with vertical Bell laboratories layered space-time (V-BLAST) detector.